The Benefits of and Challenges to Implement 5D BIM in Construction Industry - Amjed Naeem Hasan; Sawsan M. Rasheed (Civil Engineering Journal, 2019)
The Architecture, Engineering and Construction (AEC) industry is known as one of the prominent sectors contributing to economic in Iraq. On the other hand, this sector suffers from poor quality, poor communication, and cost overruns and delay project completion. Time and cost estimation are two major critical processes in construction management, to conduct estimation must plans and specification are completed. Manually estimate is time consuming and error prone because human activities. Building information modelling (BIM) can be used to automate these processes in short time and accurate estimate, BIM is a relative new technology in architect, engineering, and construction industry (AEC), which has a major effect in construction industry practices. The 3D model is the geometry model and when attached time will be 4D and 5D when attached cost. The aim of this study is to provide clear understanding about 5D BIM in Iraqi construction industry by investigating benefits, challenges, and motivation factors that helps in applying it. The results show that the awareness rate of Iraqi engineers about BIM is actually weak with 67.5% of respondents, main advantages of BIM technology are collaboration, digital representation, visualization, effective QTO tool, and reduce change order, respectively, the main challenges that facing BIM are culture resistance, thoughts recent software and traditional approach are enough of 5D BIM tools, respectively; the main motivation factors that help in BIM adoption are adapted in universities and government support. The Iraqi construction industry is remained behind in adopting the BIM capabilities related to time (4D BIM) and cost management (5D BIM). This research helps as a stepping-stone to study further to promoting BIM application in the Iraqi construction industry.